Lithium complexes of neutral bis-NHC ligands - Brendel, Matthias; Wenz, Jan; Shishkov, Igor V.; Rominger, Frank; Hofmann, Peter (Organometallics, 2015)
The employment of lithium hexamethyldisilazide for the deprotonation of methylene-bridged bis(imidazolium) salts led to the formation of lithium carbene adducts. Depending on the crystallization method and the substituents of the ligands, monomeric, dimeric, or polymeric solid-state structures were obtained. These lithium carbene complexes represent the first examples of lithium complexes bearing neutral bis(N-heterocyclic carbene) ligands.